Game Edukasi Database, Algorithm and Network Dalam Tiga Bahasa Berbasis Android - Ratnawati; Rizal; Markani Kania; Butsiarah; Aminah (Journal Software, Hardware and Information Technology, 2021)
This research aims to design a dalnet educational game with the adventure genre that can assist students in understanding database, algorithm and network subject matter. As a learning medium to increase interest in learning in informatics engineering students and information systems. In this game, the score is used as the output of the game. The results showed that the application of database, algorithm and network educational games in three languages that got the results of the feasibility test of the system and game testing designed by 88.3%. In addition no specific smartphone specifications are used.